(3LGeY GdeYGQa hGdCMcGes - (3GdMSjfj, GdcGXej, oTnqHQ, GdeLdSj GdKGfj, YHO Gddg Hf eMeO QVG Bd THQ, J (B1242(3g`s ((3HNW eDdagGs)
(3ChdgG (B:s
(3GdMeO ddg GdPj aVd GdeLGgOjf Ydi GdbGYOjf OQLGJ(B...(3CeG HYO agPG gh GdeLdO GdSGOS hgh cJGH GdLgGO ef cJGH GdCMcGe(B...s
(3BNQgG (B:s
...(3Yf CHj YHO Gddg Y bGd bGd QShd Gddg (B-(3Udi Gddg Ydjg hSde(B- (3cd HOYI VdGdI hcd VdGdI aj GdfGQ Gddge LfHfG GdGHJOGY hGJHGY Gdghi(B...(3Je cJGH GdLgGOs
(3ajgG GVWQGH aj JQJjH HYV GdChQGb, aLGAJ GdChQGb GdChdi aj fgGjI GdeNWhWIs
(3JHUQI GdYfhGf (B:s
(3LGeY GdCMcGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B2(3,U(B279s
(3GdPQjYI(B:(3L(B5(3,U(B50(3,Qbe(B281s
Keywords: (3abg GdePGgH GdCNQis